Effects of Anthocyanin Supplementation on Serum Lipids, Glucose, Markers of Inflammation and Cognition in Adults With Increased Risk of Dementia – A Pilot Study - Bergland, Anne Katrine; Soennesyn, Hogne; Dalen, Ingvild; Rodriguez-Mateos, Ana; Berge, Rolf Kristian; Giil, Lasse Melvaer; Rajendran, Lawrence; Siow, Richard; Tassotti, Michele; Larsen, Alf Inge; Aarsland, Dag (Frontiers in Genetics, 2019)
Background: Anthocyanins may protect against cognitive decline and dementia. Objective: Open-label study to measure changes in serum lipids, glucose, glycosylated hemoglobin (HbA1c), and markers of inflammation after anthocyanin supplementation in people with increased risk of dementia. Methods: 27 people with mild cognitive impairment (MCI) (n=8) or stable coronary artery disease (CAD) (n=19) consumed two Medox® capsules, each containing 80 mg of natural purified anthocyanins, twice daily for 16 weeks. They provided blood samples and performed a short battery of cognitive tests. Twenty healthy normal controls (NC) (n=20) provided blood samples, but did not receive any intervention and did not perform cognitive tests. Results: There was a significant difference between groups for CCL-5/RANTES (regulated on activation, normal T-cell expressed and secreted) (RANTES). In addition, total cholesterol and triglycerides were significantly increased in the anthocyanin group. Some of the cognitive test scores significantly improved. No adverse effects were observed. Conclusion: The results of this pilot study were largely inconclusive with regard to the potential protective effects of anthocyanin supplementation. However, anthocyanins were well tolerated, and compliance was high. Larger, placebo-controlled studies to explore the potential effects of anthocyanin on dementia risk are encouraged.